Pharmacogenomic analysis of alarelin acetate-induced hepatotoxicity: a case report and literature review - Yuan, Fang; Zhang, Ping; Liu, Ming; Li, Yuan; Xu, Bin; Li, Xin (Frontiers in Medicine, 2025)
BackgroundAlarelin acetate, a synthetic gonadotropin-releasing hormone (GnRH) analogue, is widely used to manage endometriosis and hormone-sensitive malignancies. Although its safety profile is generally favorable, we report the first documented case of severe hepatotoxicity associated with alarelin acetate administration.Case summaryA 37-year-old female participant in a phase I clinical trial developed acute hepatocellular injury following subcutaneous administration of alarelin acetate (150 μg/day). The Roussel Uclaf Causality Assessment Method (RUCAM) yielded a score of 6, indicating a “highly probable” causal relationship between the drug and liver injury. Hepatic enzyme levels normalized within 18 days after drug discontinuation and initiation of hepatoprotective therapy (glycyrrhizin and polyene phosphatidylcholine). Pharmacogenomic profiling identified specific genetic variations that may be associated with alarelin acetate-related hepatotoxicity, including a homozygous NUDT15 variant (*3/*3 diplotype) and human leukocyte antigen (HLA) risk alleles (HLA-DRB1*15:01, HLA-DQB1*06:01).ConclusionThis novel case highlights the risk of alarelin acetate-related hepatotoxicity. Pharmacogenomic profiling indicated that its hepatotoxicity may be related to gene polymorphisms; however, further research or larger-scale studies are needed to validate these associations.